A method for preparing mesoporous catalyst based on activated alumina

The method of preparing an intermediate pore size catalyst with tungsten and nickel loading on γ-oxidized aluminum addresses the limitations of existing catalysts by enhancing surface area, acidity, and stability, achieving high hydrodesulfurization efficiency and prolonged catalytic performance.

CN118788355BActive Publication Date: 2025-03-18JIANGSU JINGJING NEW MATERIALS
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411291432.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2025-03-18
Estimated Expiration
2044-09-14

AI Technical Summary

Technical Problem

Current catalysts for oil refining, particularly those using γ-oxidized aluminum, face limitations such as low surface area, unstable pore structure, low acidity, and poor catalytic efficiency and stability during hydrodesulfurization processes.

Method used

A method for preparing an intermediate pore size catalyst using a combination of silicon ethoxide and aluminum with a dual metal loading of tungsten and nickel on γ-oxidized aluminum, employing a hard and soft template with controlled acid treatment and ultrasonic processing to enhance surface area, pore structure, and acid content.

Benefits of technology

The catalyst achieves high hydrodesulfurization efficiency with a conversion rate of up to 59.7% after 10 cycles, demonstrating improved stability and catalytic performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118788355B_ABST
    Figure CN118788355B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of catalyst technology, specifically to a method for preparing a mesoporous catalyst based on activated alumina. The present invention hydrolyzes ethyl orthosilicate and aluminum sec-butoxide together, mixes with a hard template and a soft template, introduces hydrogen, loads tungsten and nickel bimetallics after calcination, and then calcines again and acid-treats and ultrasonically obtains a mesoporous catalyst. By silicon-modifying alumina and controlling the calcination procedure, the obtained catalyst has a large specific surface area and pore volume; by controlling the addition of a hard template, a soft template and hydrogen, the obtained catalyst has a mesoporous structure and a stable pore configuration; tungsten and nickel are loaded on the activated alumina, the pH of the system, the ratio and total amount of metals are controlled, and the catalyst has high activity for the hydrodesulfurization reaction of sulfur-containing dibenzothiophene; by acid treatment and ultrasonication, the B acid amount, L acid amount and total acid amount of the catalyst are all improved; by protecting the hydrolysis site of alumina, the obtained catalyst has a good catalytic effect after 10 cycles of use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalysts, and in particular to a method for preparing a mesoporous catalyst based on activated alumina. Background Art

[0002] In the process of industrial production, alumina is widely used in technical fields such as multiphase catalysts and catalyst carriers. Among the many crystal phases of alumina, γ-alumina has the best performance. It has the advantages of adjustable pore properties, large specific surface area, strong adsorption, adjustable surface acidity and alkalinity, high mechanical strength and high thermal stability. Therefore, it is also called activated alumina.

[0003] As a non-renewable resource, the reserves of petroleum are gradually decreasing. It is very important to fully separate and purify the oil after it is extracted, which directly affects the utilization rate of the oil and the maximum benefit. Among them, hydrodesulfurization technology has shown excellent performance in the purification of sulfur-rich fuels, but it also faces some technical problems, such as low sulfur removal rate, low catalytic activity of the catalyst, and low final product conversion rate. In order to solve these technical problems, alumina is widely used as a carrier of catalysts. Patent CN201811226380.5 discloses a modified alumina carrier, a preparation method thereof, and a hydrorefining catalyst, in which a silane coupling agent is added for modification, and the specific surface area of ​​the obtained carrier material is 300-400m 2 / g, pore volume is 0.5-0.8cm 3 / g, with an average pore size of 7-9nm, and has good desulfurization rate and hydrogenation activity.

[0004] Patent CN201711220716.2 discloses a heavy fraction oil hydroprocessing catalyst and its application, using hexadecyltrimethylammonium bromide or hexadecyltrimethylammonium chloride as a template, and the obtained catalyst has good hydrodesulfurization and hydrodenitrogenation activity for heavy petroleum fractions, but the template is single, and the acid content of the catalyst is low, and the catalytic conversion rate needs to be improved. Patent CN201910698176.1 discloses a supported nickel phosphide catalyst and its preparation method, using a composite composed of mesoporous-macroporous ZSM-5 molecular sieve and alumina as a catalyst carrier, and the acidity is adjustable. In order to improve the catalytic effect of the catalyst, metal elements are widely used, and platinum is widely used, but as a scarce metal element, its use cost is high. Molybdenum and nickel are also used in the catalytic process, such as Wang W, Li L, Tan S, et al. Preparation of NiS, / MoS, cata-lysts by two-step hydrothemal method and their enhanced activity for hydrodeoxygenation of peresol [J]. Fuel, 2016.179: 1-9. Nickel and molybdenum are introduced into the reaction system, and nano-carriers are prepared by hydrothermal method. The hydrodeoxygenation of cresol is highly efficient, but the catalytic cycle and stability are poor. Patent CN201910556370.6 discloses a residual oil hydrodemetallization desulfurization catalyst and its preparation method, which uses metal tungsten and nickel to load on an alumina carrier, and adds cerium and titanium metal elements to obtain a catalyst. The catalyst can achieve the effect of deep desulfurization and denitrification, but the specific surface area is low relative to activated alumina. Patent CN201310035314.0 discloses a transition metal phosphide hydrogenation catalyst and its preparation method, which uses amorphous silicon aluminum, macroporous alumina, and mesoporous molecular sieves as carriers to load tungsten, nickel, and phosphorus. The resulting catalyst can achieve the purpose of deep desulfurization and denitrification.

[0005] Although certain progress has been made in the research of catalysts using alumina as a carrier, the catalyst still has many disadvantages in the hydrodesulfurization of oil components, such as small specific surface area of ​​the catalyst, unstable pore structure of the catalyst, low acid content of the catalyst, poor catalytic effect and poor catalytic recyclability.

[0006] To this end, a method for preparing a mesoporous catalyst based on activated alumina is proposed. Summary of the invention

[0007] The purpose of the present invention is to provide a method for preparing a mesoporous catalyst based on activated alumina, wherein ethyl orthosilicate and aluminum sec-butoxide are co-hydrolyzed, mixed with a hard template and a soft template, and then hydrogen is introduced, calcined to load tungsten and nickel bimetallics, calcined again, and then acid-treated and ultrasonicated to obtain a mesoporous catalyst. The catalyst is modified by using ethyl orthosilicate, and a cross-linked three-dimensional gel is formed by hydrothermal reaction. The catalyst obtained by calcination has a specific surface area of ​​278-372m 2 ·g -1 , pore volume is 1.94-2.61cm 3 ·g -1 , with an average pore size of 11.90-17.30nm. By mixing a hard template and a soft template as a porogen and introducing H2 as a structure-directing agent, the catalyst obtained has an ink bottle pore shape inside and a large specific surface area. By simultaneously loading tungsten and nickel metals on activated alumina and controlling the ratio and dosage of the two metals, the obtained catalyst is used to catalyze the hydrodesulfurization reaction of sulfur-containing dibenzothiophene, with good catalytic effect and high conversion rate. By treating with hydrochloric acid, controlling the concentration of the acid treatment and the conditions of the ultrasonic treatment, the obtained catalyst B has an acid content of 1.93-2.85µmol / g, the L has an acid content of 20.49-25.91µmol / g, and the total acid content is 23.05-28.76µmol / g. The activated alumina was modified by silicon and loaded with tungsten and nickel bimetallics. The catalyst formed various types of chemical bonds. After 10 cycles, it was used to catalyze the hydrodesulfurization reaction of sulfur-containing dibenzothiophene, and the conversion rate could reach 59.7%. The catalyst has good recyclability.

[0008] To achieve the above object, the present invention provides the following technical solutions:

[0009] In one aspect, the present invention provides a method for preparing a mesoporous catalyst based on activated alumina, characterized in that it comprises the following steps:

[0010] Aluminum sec-butoxide is dissolved in isopropanol to obtain an aluminum sec-butoxide solution; 0-6.25 g of ethyl orthosilicate and 3.1-9.3 mL of deionized water are added to the aluminum sec-butoxide solution, and the mixture is hydrolyzed for 3.5-5 h under stirring and heating to obtain a mixed solution; the mixed solution is hydrothermally reacted for 2 h to obtain a gel; the gel is vacuum filtered, washed and dried to obtain silica-pseudo-boehmite; the silica-pseudo-boehmite, a hard template and a soft template are ball-milled in a mass ratio of 10:0-6.5:0-2 to obtain a mixture; the mixture is placed in a tubular furnace, and 0.3-1.5 MPa of H2 is introduced after N2 is used, and the temperature is first increased at a rate of 2.5-4°C / min, and calcined at a temperature of 600-800°C for 3.5-4.0 h to obtain activated alumina;

[0011] The activated alumina is dispersed in deionized water, and the pH is adjusted to 1.5-4.0 to obtain an activated alumina dispersion; a sodium tungstate solution is mixed with a nickel acetate tetrahydrate solution to obtain a metal solution; the molar mass ratio of tungsten to nickel in the metal solution is 0-11:0-10; the activated alumina dispersion is mixed with the metal solution, ammonia water is added dropwise and the mixture is placed in an oven to be dried to obtain a material to be calcined; the total mass of tungsten and nickel in the material to be calcined is 0.06-0.22 mg; the material to be calcined is placed in the tubular furnace again, heated for a second time at a rate of 5-8°C / min, and calcined at 800°C for 2h to obtain an intermediate; a hydrochloric acid solution with a volume fraction of 0-60% is added to the intermediate, and ultrasonicated at a frequency of 80-120HZ for 8-30min, and then centrifuged, washed and dried to obtain the mesoporous catalyst based on activated alumina.

[0012] Preferably, the concentration of the aluminum sec-butoxide solution is 0.05 g / mL; and the amount of the tetraethyl orthosilicate used is 1.04-6.25 g.

[0013] Preferably, the hard template is nano calcium carbonate.

[0014] Preferably, the soft template is any one of hexadecyltrimethylammonium bromide, pre-treated chitosan, polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer, polyether polyol and sodium dodecyl sulfate.

[0015] Preferably, the method for preparing the pre-treated chitosan comprises: adding hydrochloric acid solution to chitosan, stirring for half an hour to completely dissolve the chitosan, and then adding ammonia water to adjust the pH to 7 to obtain the pre-treated chitosan.

[0016] Preferably, silica-pseudo-boehmite, the hard template and the soft template are added into the ball mill in a mass ratio of 10:3-6.5:1-2.

[0017] Preferably, the H2 is 0-1.5 MPa.

[0018] Preferably, the molar mass ratio of tungsten to nickel in the metal solution is 1-11:1-9.

[0019] Preferably, 100 mL of a hydrochloric acid solution having a volume fraction of 35-60% is added to the intermediate.

[0020] On the other hand, the present invention provides a mesoporous catalyst based on activated alumina, characterized in that: the mesoporous catalyst based on activated alumina is hydrolyzed with tetraethyl orthosilicate and aluminum sec-butoxide, mixed with a hard template and a soft template, and calcined by passing H2 to obtain activated alumina; the activated alumina is impregnated with tungsten and nickel and then calcined, and then treated with hydrochloric acid solution, ultrasonicated, centrifuged, washed and dried to obtain the mesoporous catalyst based on activated alumina; the mesoporous catalyst based on activated alumina is prepared by any of the preparation methods described above; the mesoporous catalyst based on activated alumina is modified by the tetraethyl orthosilicate, and the specific surface area of ​​the mesoporous catalyst based on activated alumina is 278-372m 2 ·g -1 , pore volume is 1.94-2.61cm 3 ·g -1 , the average pore size is 11.90-17.30nm; by changing the type and amount of the hard template and the soft template, the specific surface area of ​​the mesoporous catalyst based on activated alumina is 289-382m 2 ·g -1 , pore volume is 1.90-2.65cm 3 ·g -1 , the average pore size is 8.63-20.35nm; the mesoporous catalyst based on activated alumina is used for the hydrodesulfurization reaction of sulfur-containing dibenzothiophene, and the conversion rate of the raw material is in the range of 51.0%-75.3%; after using the hydrochloric acid solution and the ultrasonic treatment, the B acid amount of the mesoporous catalyst based on activated alumina is 1.93-2.85µmol / g, the L acid amount is 20.49-25.91µmol / g, and the total acid amount is 23.05-28.76µmol / g; the conversion rate of the mesoporous catalyst based on activated alumina after the first catalysis is 60.5%-74.0%, the conversion rate after catalysis after 5 uses is 55.4%-69.5%, and the conversion rate after catalysis after 10 cycles of use is 44.2%-59.7%.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] 1. The present invention hydrolyzes tetraethyl orthosilicate and aluminum sec-butoxide together, mixes with a hard template and a soft template after hydrolysis, then adds a structure directing agent for calcination reaction, loads a metal and calcines again, and obtains a catalyst after acid treatment and ultrasound. Silicon-modified alumina is hydrolyzed to form a cross-linked three-dimensional gel through a hydrothermal reaction, and the amount of tetraethyl orthosilicate, the heating rate of calcination and the calcination temperature are controlled to obtain a mesoporous catalyst based on activated alumina with a specific surface area of ​​278-372 m 2 ·g -1 , pore volume is 1.94-2.61cm 3 ·g -1, the average pore size is 11.90-17.30nm.

[0023] 2. By mixing hard templates and soft templates as porogens, and introducing H2 as a structure-directing agent, the type and amount of the soft template and the pressure of hydrogen are controlled, and the obtained catalyst has a stable mesoporous structure. Pre-treated chitosan is used as a soft template, and the pressure of H2 is 1.5MPa. The specific surface area, pore volume and average pore size of the obtained catalyst are larger than those of the catalysts obtained under other conditions. The hard template is finally removed with hydrochloric acid; the use of the soft template allows the chitosan macromolecular structure to be used as a template to form a continuous three-dimensional network skeleton. At the same time, under the action of mechanochemistry, the amino and carboxyl groups in the chitosan molecules form a large number of hydrogen bonds. In the early stage of the subsequent calcination process, chitosan forms a gel with silica-pseudo-boehmite, and finally forms mesopores.

[0024] 3. By loading tungsten and nickel metals on activated alumina at the same time and controlling the ratio and dosage of the two metals, the obtained catalyst is used to catalyze the hydrodesulfurization reaction of sulfur-containing dibenzothiophene, with good catalytic effect and high conversion rate. Loading metals on activated silicon-modified alumina is conducive to the uniform distribution of active components, which significantly increases the number of active sites. At the same time, the appropriate pore size and pore volume provide sufficient contact space for the reactants, thereby improving the product conversion rate. Nickel has the ability to absorb electrons, causing the sulfur element to lose electrons and be removed from the reaction system; the tungsten element forms a WO-Al structure during the subsequent calcination process, which increases the acid value of the catalyst surface and improves the catalytic effect.

[0025] 4. In the final preparation method of the catalyst, hydrochloric acid and ultrasound are used to remove the hard template nano calcium carbonate, and the acid content of the catalyst is increased together with tungsten and nickel metals. By controlling the acid concentration and the frequency and time of the ultrasonic treatment, the B acid content of the obtained catalyst is 1.93-2.85µmol / g, the L acid content is 20.49-25.91µmol / g, and the total acid content is 23.05-28.76µmol / g. The catalyst has a high acid content and good catalytic activity.

[0026] 5. The activated alumina is modified with silicon and loaded with tungsten and nickel bimetallics to obtain a catalyst with good cycle performance. Three types of chemical bonds, WO-Al, Si-O-Al and Ni-O-Al, are formed during the reaction, which protect the hydrolysis sites of the activated alumina and prevent the occurrence and progress of the hydrolysis reaction of the activated alumina. The obtained catalyst is used to catalyze the hydrodesulfurization reaction of sulfur-containing dibenzothiophene. The conversion rate after the first catalysis is 60.5%-74.0%, the conversion rate after catalysis after 5 uses is 55.4%-69.5%, and the conversion rate after catalysis after 10 cycles is 44.2%-59.7%. The catalyst has strong stability and good catalytic cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a BET test result diagram of the catalyst of Example 18 of the present invention;

[0028] Figure 2 Graphs showing the XRD test results of Examples 32 and 35 of the present invention;

[0029] Figure 3 This is a graph showing the catalytic cyclic performance test results of the catalyst of Example 61 of the present invention. DETAILED DESCRIPTION

[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] See also Figures 1 to 3 The present invention provides a method for preparing a mesoporous catalyst based on activated alumina, and the technical scheme is as follows:

[0032] Information on substances involved in the present invention:

[0033] Nano calcium carbonate was purchased from Xi'an Qiyue Biotechnology Co., Ltd.;

[0034] Polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer CAS: 106392-12-5; polyether polyol CAS: 9003-11-6; hexadecyltrimethylammonium bromide CAS: 57-09-0; chitosan is ethylene glycol chitosan, CAS: 123938-86-3, and other substances are conventionally used substances in the chemical field unless otherwise specified.

[0035] The reagents used in the present invention are all analytical grade reagents.

[0036] Example 1

[0037] Aluminum sec-butoxide is dissolved in isopropanol to obtain an aluminum sec-butoxide solution; the concentration of the aluminum sec-butoxide solution is 0.05 g / mL; 2.09 g of tetraethyl orthosilicate and 3.1 mL of deionized water are added to 200 mL of the aluminum sec-butoxide solution, and the mixture is hydrolyzed at 70°C and 600 rpm for 5 hours to obtain a mixed solution; the mixed solution is heated to 120°C, and a hydrothermal reaction is performed for 2 hours to obtain a gel; the gel is vacuum filtered, washed, and dried to obtain silica-pseudo-boehmite; silica-pseudo-boehmite, a hard template agent, and a soft template agent are added to a ball mill in a mass ratio of 10:5:1.8, and ball milled for 3 hours to obtain a mixture; the hard template agent is nano-calcium carbonate; the mixture is placed in a tubular furnace, the air in the tubular furnace is replaced by N2, and then 1.5 MPa of H2 is introduced, and the temperature is first increased at a rate of 4°C / min, and the temperature is increased to 800°C for the first calcination, and the activated alumina is obtained by calcination for 3.5 hours;

[0038] Disperse 50 mg of the activated alumina in 30 mL of deionized water, and adjust the pH to 3.5 to obtain an activated alumina dispersion; dissolve sodium tungstate dihydrate in deionized water to obtain a sodium tungstate solution; dissolve nickel acetate tetrahydrate in deionized water to obtain a nickel acetate tetrahydrate solution; mix the sodium tungstate solution with the nickel acetate tetrahydrate solution to obtain a tungsten-nickel metal solution; the molar mass ratio of tungsten (W) to nickel (Ni) in the tungsten-nickel metal solution is 3:1; mix the activated alumina dispersion with the tungsten-nickel metal solution, drop ammonia water and dry in an oven to obtain a material to be calcined; The total mass of the tungsten and the nickel in the material to be calcined is 0.12 mg; the material to be calcined is placed in a tubular furnace again, and the temperature is increased for a second time at a rate of 8°C / min. After the temperature is increased to 800°C, a second calcination is performed, and the intermediate is calcined for 2 hours; 100 mL of a 50% by volume hydrochloric acid solution is added to the intermediate, and the metal-loaded mesoporous alumina is obtained by ultrasonication at a frequency of 100 Hz for 10 minutes; the metal-loaded mesoporous alumina is centrifuged, washed with deionized water, and dried to obtain a mesoporous catalyst based on activated alumina.

[0039] Example 2-15

[0040] Different from Example 1, the following preparation conditions are changed, as shown in Table 1.

[0041] Table 1 Conditions for the preparation of mesoporous catalysts based on activated alumina

[0042] Group Addition amount of tetraethyl orthosilicate (g) Amount of deionized water added (mL) Hydrolysis time (h) First heating rate (℃ / min) Heating temperature (℃) First calcination time (h) Second heating rate (℃ / min) Example 2 2.09 3.4 5 4 800 3.5 8 Example 3 2.09 4.9 5 4 800 3.5 8 Example 4 2.09 6.5 5 4 800 3.5 8 Example 5 2.09 7.0 5 4 800 3.5 8 Example 6 2.09 8.5 5 4 800 3.5 8 Example 7 2.09 9.3 5 4 800 3.5 8 Example 8 2.09 4.9 4 4 800 3.5 8 Example 9 2.09 4.9 3.5 4 800 3.5 8 Example 10 1.04 1.2 3.5 4 800 3.5 8 Embodiment 11 4.17 1.9 3.5 4 800 3.5 8 Example 12 6.25 2.6 3.5 2.5 800 3.5 8 Example 13 2.09 4.9 3.5 4 700 3.5 8 Embodiment 14 2.09 4.9 3.5 4 600 3.5 8 Embodiment 15 2.09 4.9 3.5 4 800 3.5 5

[0043] Comparative Example 1

[0044] Different from Example 1, the addition amount of tetraethyl orthosilicate is 0 g, and the first and second calcination temperatures are 600° C.

[0045] Comparative Example 2

[0046] The difference from Example 1 is that the amount of tetraethyl orthosilicate added is 0 g.

[0047] Example 16

[0048] The specific surface area, pore volume and average pore diameter of the mesoporous catalysts based on activated alumina prepared in Examples 1-15 and Comparative Examples 1 and 2 were measured using a BET specific surface area tester 3H-2000BET-M. The pore size distribution was calculated using the BJH model based on the isothermal adsorption curve of the sample to obtain the pore size distribution test results. The measurement results are recorded in Table 2.

[0049] Table 2 BET parameters of catalysts of Examples 1-15 and Comparative Examples 1 and 2

[0050] Group BET specific surface area (m2 g-1) Pore ​​volume (cm3·g-1) Average pore size (nm) Example 1 278 1.99 12.07 Example 2 286 1.94 12.50 Example 3 302 2.21 13.65 Example 4 312 2.40 11.90 Example 5 304 2.35 12.63 Example 6 305 2.30 14.21 Example 7 294 2.44 15.12 Example 8 335 2.39 12.01 Example 9 372 2.61 15.94 Example 10 326 2.18 13.11 Embodiment 11 344 2.39 14.56 Example 12 350 2.57 17.30 Example 13 345 2.35 14.35 Embodiment 14 323 2.50 15.87 Embodiment 15 330 2.08 12.33 Comparative Example 1 316 2.16 11.89 Comparative Example 2 295 1.90 7.90

[0051] As shown in Table 2, the specific surface area of ​​the mesoporous catalyst based on activated alumina obtained in the example is 278-372 m 2 ·g -1 , pore volume is 1.94-2.61cm 3 ·g -1 , with an average pore size of 11.90-17.30 nm. In Examples 1-7, as the volume of deionized water increases, the specific surface area increases first and then decreases, and the pore volume is 1.99-2.44 cm 3 ·g -1 , the pore size is 11.90-15.12nm; by introducing tetraethyl orthosilicate into the mesoporous reaction system of activated alumina, tetraethyl orthosilicate undergoes hydrolysis reaction with water molecules, and aluminum sec-butoxide also undergoes hydrolysis under the action of water, and a three-dimensional gel is obtained by crosslinking through a hydrothermal reaction. When the amount of water added is too high, the forward reaction of tetraethyl orthosilicate is not complete, resulting in a decrease in specific surface area. However, compared with the mesoporous catalyst of activated alumina without adding tetraethyl orthosilicate in Comparative Example 1, the specific surface area, pore volume and average pore size are increased overall. Example 4 is compared with the results of Examples 8 and 9. The hydrolysis time is 3.5h. As shown in Example 9, the catalyst obtained has the largest specific surface area of ​​372m 2 ·g -1 , the pore volume is the highest, which is 2.61cm 3 ·g -1, the appropriate hydrolysis time makes the catalyst have a larger specific surface area and pore volume. From the comparison of the results of Examples 9-12, it can be seen that with the increase in the amount of tetraethyl orthosilicate added, the specific surface area shows a trend of increasing, decreasing and increasing. When the amount of tetraethyl orthosilicate added is not appropriate, as shown in Example 11, it may cause pore blockage inside the mesoporous alumina, resulting in a decrease in specific surface area, pore volume and pore diameter compared with Comparative Examples 1 and 2. From the comparison of the results of Example 9 and Examples 13-15, it can be seen that low calcination temperature or heating rate lower than 8°C / min will lead to different degrees of reduction in specific surface area, pore volume and average pore diameter. Comparative Example 2 does not add tetraethyl orthosilicate, and the calcination temperature is 800°C. The pore volume and average pore diameter of the mesoporous catalyst based on activated alumina are the lowest. Since tetraethyl orthosilicate is not introduced, the tolerance temperature of the catalyst material is lower than that of the embodiment and Comparative Example 1. The catalyst pores collapse under high-temperature calcination, so the pore volume and average pore diameter are reduced.

[0052] Examples 17-28

[0053] Aluminum sec-butoxide was dissolved in isopropanol to obtain an aluminum sec-butoxide solution; the concentration of the aluminum sec-butoxide solution was 0.05 g / mL; 2.09 g of ethyl orthosilicate and 4.9 mL of deionized water were added to 200 mL of the aluminum sec-butoxide solution, and the mixture was hydrolyzed at 70° C. and 600 rpm for 3.5 h to obtain a mixed solution; the mixed solution was heated to 120° C. and subjected to hydrothermal reaction for 2 h to obtain a gel; the gel was vacuum filtered, washed, and dried to obtain a silicon-pseudo-thin diaspore; adding silica-pseudo-boehmite, hard template and soft template in a mass ratio of 10:5:1.5 into a ball mill, and ball milling for 3 hours to obtain a mixture; the hard template is nano-calcium carbonate; placing the mixture in a tubular furnace, using N2 to replace the air in the tubular furnace, and then introducing 1.5MPa of H2, heating at a rate of 4°C / min for the first time, and calcining for the first time after the temperature is raised to 800°C, and calcining for 3.5 hours to obtain activated alumina;

[0054] Disperse 50 mg of the activated alumina in 30 mL of deionized water, and adjust the pH to 3.5 to obtain an activated alumina dispersion; dissolve sodium tungstate dihydrate in deionized water to obtain a sodium tungstate solution; dissolve nickel acetate tetrahydrate in deionized water to obtain a nickel acetate tetrahydrate solution; mix the sodium tungstate solution and the nickel acetate tetrahydrate solution to obtain a tungsten-nickel metal solution; the molar mass ratio of tungsten to nickel in the tungsten-nickel metal solution is 3:1; mix the activated alumina dispersion with the tungsten-nickel metal solution, add ammonia water and dry in an oven to obtain a material to be calcined; the material to be calcined The total mass of the tungsten and the nickel in the material is 0.12 mg; the material to be calcined is placed in a tube furnace again, and the temperature is raised for the second time at a rate of 8°C / min. After the temperature is raised to 800°C, the second calcination is performed, and the intermediate is calcined for 2 hours; 100 mL of a 50% volume fraction hydrochloric acid solution is added to the intermediate, and the metal-loaded mesoporous alumina is obtained by ultrasonication at a frequency of 100 Hz for 10 minutes; the metal-loaded mesoporous alumina is centrifuged, washed with deionized water, and dried to obtain a mesoporous catalyst based on activated alumina. The specific preparation information is shown in Table 3.

[0055] Table 3 Mass ratio of medium-silica-pseudo-boehmite to nano-calcium carbonate and soft template and H2 injection pressure of Examples 17-28

[0056] Group Types of soft templates The ratio of the amount of substance added H2 injection pressure (MPa) Embodiment 17 Hexadecyltrimethylammonium bromide 10:5:1.5 1.5 Embodiment 18 Pre-treatment of chitosan 10:5:1.5 1.5 Embodiment 19 Polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer 10:5:1.5 1.5 Embodiment 20 Polyether polyols 10:5:1.5 1.5 Embodiment 21 Sodium Lauryl Sulfate 10:5:1.5 1.5 Embodiment 22 Pre-treatment of chitosan 10:5:2.0 1.5 Embodiment 23 Pre-treatment of chitosan 10:5:1.0 1.5 Embodiment 24 Pre-treatment of chitosan 10:4:1.5 1.5 Embodiment 25 Pre-treatment of chitosan 10:3:1.5 1.5 Embodiment 26 Pre-treatment of chitosan 10:6.5:1.5 1.5 Embodiment 27 Pre-treatment of chitosan 10:5:1.5 1.0 Embodiment 28 Pre-treatment of chitosan 10:5:1.5 0.3

[0057] Embodiment 18

[0058] The preparation method of the pre-treated chitosan is as follows: adding hydrochloric acid with a mass concentration of 10% of the mass of the chitosan to the chitosan, wherein the mass concentration of the hydrochloric acid is 40%, stirring for half an hour to completely dissolve the chitosan, and then adding ammonia water to adjust the pH to 7 to obtain the pre-treated chitosan.

[0059] Comparative Example 3

[0060] Different from Example 17, no hard template nano calcium carbonate was added.

[0061] Comparative Example 4

[0062] Different from Example 17, the soft template agent hexadecyltrimethylammonium bromide was not added.

[0063] Comparative Example 5

[0064] Different from Example 17, H2 was not introduced.

[0065] Embodiment 29

[0066] The performance of the mesoporous catalysts based on activated alumina prepared in Examples 17-28 and Comparative Examples 3-5 was measured, and the measured indicators included specific surface area, pore volume and average pore diameter. The test method was carried out according to the method of Example 16, and the final test results are shown in Table 4. The BET test results of the catalyst obtained in Example 18 are shown in Table 4. Figure 1 shown.

[0067] Table 4 BET test results of catalysts of Examples 17-28 and Comparative Examples 3-5

[0068] Group BET specific surface area (m2 g-1) Pore ​​volume (cm3·g-1) Average pore size (nm) Embodiment 17 371 2.66 20.35 Embodiment 18 380 2.65 18.18 Embodiment 19 365 2.52 17.02 Embodiment 20 320 2.37 16.41 Embodiment 21 306 2.40 16.70 Embodiment 22 345 2.65 17.93 Embodiment 23 338 2.23 15.91 Embodiment 24 318 2.12 12.65 Embodiment 25 299 2.01 9.71 Embodiment 26 382 2.04 15.64 Embodiment 27 341 2.35 16.18 Embodiment 28 289 1.90 8.63 Comparative Example 3 253 1.81 8.21 Comparative Example 4 315 2.20 11.27 Comparative Example 5 291 1.95 8.55

[0069] As shown in Table 4, the specific surface area of ​​the catalyst prepared in the embodiment of the present invention is 289-382m 2 ·g -1 , pore volume is 1.90-2.65cm 3 ·g -1 , the average pore size is 8.63-20.35nm. In Examples 17-21, by changing the type of soft template, the obtained catalyst has a higher specific surface area, pore volume and average pore size. The soft template is evenly distributed in silica-pseudo-boehmite after grinding. As the calcination process proceeds, these compounds form a gas escape reaction system through sublimation, thereby forming uniform and dense mesopores in the system; the soft template in Example 18 is pre-treated chitosan, and a small amount of hydrochloric acid is added to dissolve the chitosan. After ball milling with the hard template and silica-pseudo-boehmite, a continuous three-dimensional network skeleton is formed with the chitosan macromolecular structure as a template. At the same time, under the action of mechanochemistry, the amino and carboxyl groups in the chitosan molecules form a large number of hydrogen bonds. In the early stage of the subsequent calcination process, the chitosan forms a gel with the silica-pseudo-boehmite, and finally forms mesopores. As Figure 1 As shown, the hysteresis loop type of the nitrogen adsorption-desorption curve of the catalyst prepared in Example 18 is H2 type, indicating that the catalyst prepared by the present invention is a mesoporous structure, and the pore configuration is a relatively stable ink bottle-shaped pore. Comparing the results of Examples 22-23 with those of Example 18, it can be seen that the soft template agent needs to maintain a reasonable ratio with the other two components. The results of Examples 24-26 and Example 18 show that when the other two components remain unchanged, with the increase in the amount of calcium carbonate, the specific surface area gradually increases, but the pore volume and pore size decrease. As shown in Example 26, calcium carbonate plays a pore-forming role, and finally hydrochloric acid is added for removal. When the amount of calcium carbonate added is too large, it may cause the collapse of some pores. The results of Example 18 and Examples 27 and 28 show that by controlling the pressure of hydrogen in the range of 0.3-1.5MPa, a good structural guidance effect can be achieved.

[0070] Examples 30-41

[0071] Aluminum sec-butoxide was dissolved in isopropanol to obtain an aluminum sec-butoxide solution; the concentration of the aluminum sec-butoxide solution was 0.05 g / mL; 2.09 g of ethyl orthosilicate and 4.9 mL of deionized water were added to 200 mL of the aluminum sec-butoxide solution, and the mixture was hydrolyzed at 70° C. and 600 rpm for 3.5 h to obtain a mixed solution; the mixed solution was heated to 120° C. and subjected to hydrothermal reaction for 2 h to obtain a gel; the gel was vacuum filtered, washed, and dried to obtain silicon-pseudo-silicon water Aluminium stone; adding silica-pseudo-boehmite, hard template and pre-treated chitosan in a mass ratio of 10:5:1.5 into a ball mill, and ball milling for 3 hours to obtain a mixture; the hard template is nano calcium carbonate; placing the mixture in a tubular furnace, using N2 to replace the air in the tubular furnace, and then introducing 1.5MPa of H2, heating at a rate of 4°C / min for the first time, and calcining for the first time after the temperature is raised to 800°C, and calcining for 3.5 hours to obtain activated alumina;

[0072] Disperse 50 mg of the activated alumina in 30 mL of deionized water, and use hydrochloric acid to adjust the pH to 3.5 to obtain an activated alumina dispersion; dissolve sodium tungstate dihydrate in deionized water to obtain a sodium tungstate solution; dissolve nickel acetate tetrahydrate in deionized water to obtain a nickel acetate tetrahydrate solution; mix the sodium tungstate solution and the nickel acetate tetrahydrate solution to obtain a tungsten-nickel metal solution; the molar mass ratio of tungsten to nickel in the tungsten-nickel metal solution is 3:1; mix the activated alumina dispersion with the tungsten-nickel metal solution, add ammonia water and dry in an oven to obtain the material to be calcined; The total mass of the tungsten and the nickel in the calcined material is 0.06 mg; the material to be calcined is placed in a tubular furnace again, and the temperature is increased for a second time at a rate of 8°C / min. After the temperature is increased to 800°C, a second calcination is carried out, and the intermediate is calcined for 2 hours; 100 mL of a 50% by volume hydrochloric acid solution is added to the intermediate, and the metal-loaded mesoporous alumina is obtained by ultrasonication at a frequency of 100 Hz for 10 minutes; the metal-loaded mesoporous alumina is centrifuged, washed with deionized water, and dried to obtain a mesoporous catalyst based on activated alumina.

[0073] The detailed information of the preparation process of the embodiment is shown in Table 5.

[0074] Table 5 Preparation information of metal-loaded mesoporous alumina and catalytic activity of catalysts

[0075] Group pH n(W):n(Ni) Total mass of tungsten and nickel (mg) Conversion rate (%) Embodiment 30 3.5 3:1 0.06 62.8 Embodiment 31 4.0 3:1 0.06 51.0 Embodiment 32 3.0 3:1 0.06 74.5 Embodiment 33 2.5 3:1 0.06 74.0 Embodiment 34 1.5 3:1 0.06 67.2 Embodiment 35 3.0 1:1 0.06 74.7 Embodiment 36 3.0 3:2 0.06 66.4 Embodiment 37 3.0 2:3 0.06 72.7 Embodiment 38 3.0 3:1 0.09 74.9 Embodiment 40 3.0 3:1 0.14 75.3 Embodiment 41 3.0 3:1 0.22 74.0 Comparative Example 6 3.0 0:10 0.06 47.2 Comparative Example 7 3.0 10:0 0.06 36.7 Comparative Example 8 3.0 n(W):n(Pt)=3:1 0.06 75.8

[0076] Embodiment 42

[0077] The catalytic activity of the catalysts prepared in Examples 30-41 and Comparative Examples 6-8 was tested. The specific test method is as follows: 100 g of dibenzothiophene with a sulfur content of 17.3% was dissolved in DMF, and 0.15 g of the mesoporous catalyst based on activated alumina obtained in Examples 30-41 and Comparative Examples 6 and 7 were added and mixed evenly. The gas in the reactor was replaced 5 times with H2 in a high-pressure reactor to ensure that the reactor was in a H2 atmosphere. The reaction temperature was adjusted to 230°C and the speed was 300 rpm for 10 hours. After the reaction was completed, the product was passed into a gas chromatograph to analyze the content of dibenzothiophene in the product, and the conversion rate of dibenzothiophene was calculated. The conversion rate results are recorded in Table 5. In addition, the catalysts obtained in Examples 32 and 35 were characterized using a DX-2700 X-ray diffraction analyzer. The XRD test results are shown in Table 5. Figure 2 shown.

[0078] As shown in Table 5, the catalyst prepared in the embodiment of the present invention is used for the hydrodesulfurization reaction of sulfur-containing dibenzothiophene, and the conversion rate of the raw material is in the range of 51.0%-75.3%. The present invention prepares a mesoporous catalyst based on activated alumina, catalyzes dibenzothiophene, achieves the effect of hydrodesulfurization, has a high conversion rate of raw materials, and has potential application value in the purification of sulfur-rich fuels. In Examples 30-34, by adjusting the pH of the system, the dibenzothiophene removal rate obtained is in the range of 51.0%-74.5%, wherein the conversion rate is the highest when the pH of Example 32 is 3.0. The catalytic results of Examples 32, 35-37 show that the catalytic effects of mesoporous alumina catalysts loaded with different metal content ratios are different, and with the increase of tungsten in tungsten and nickel metals, the conversion rate shows a trend of increasing, decreasing and increasing. The present invention loads the metal on active silicon-modified alumina. The large specific surface area of ​​alumina is conducive to the uniform distribution of active components, which significantly increases the number of active sites. At the same time, the appropriate pore size and pore volume provide sufficient contact space for the reactants, thereby improving the conversion rate. Nickel has the ability to absorb electrons, causing the sulfur element to lose electrons and be removed from the reaction system; the tungsten element forms a WO-Al structure during the subsequent calcination process, which increases the acid value of the catalyst surface and improves the catalytic effect. Figure 2As shown, the XRD spectrum shows that the mesoporous catalyst based on activated alumina is consistent with the PDF#98-000-0059 card, and the metal load hinders the formation of part of the alumina crystal phase. The XRD spectrum results of Examples 32 and 35 show that the loaded metal tungsten and nickel need to be reasonably proportioned. The test results of Examples 32, 38-40 show that with the increase of the tungsten and nickel metal loading in the catalyst, the conversion first increases and then decreases. The catalyst catalyzed by Example 40 has the highest product conversion rate of 75.3%. In Comparative Examples 6 and 7, only tungsten or nickel is loaded, and the conversion rate is greatly reduced, indicating that the two metals synergistically play a role in improving the catalytic activity. In Comparative Example 8, nickel is replaced with precious metal platinum, and the final conversion rate is 75.8%. The catalytic effect of the catalyst prepared by the present invention is comparable to it. From the perspective of cost saving, nickel is used as the loaded metal.

[0079] Embodiment 43

[0080] Aluminum sec-butoxide was dissolved in isopropanol to obtain an aluminum sec-butoxide solution; the concentration of the aluminum sec-butoxide solution was 0.05 g / mL; 2.09 g of ethyl orthosilicate and 4.9 mL of deionized water were added to 200 mL of the aluminum sec-butoxide solution, and the mixture was hydrolyzed at 70° C. and 600 rpm for 3.5 h to obtain a mixed solution; the mixed solution was heated to 120° C. and subjected to hydrothermal reaction for 2 h to obtain a gel; the gel was vacuum filtered, washed, and dried to obtain silicon-pseudo-silicon water Aluminium stone; adding silica-pseudo-boehmite, hard template and pre-treated chitosan in a mass ratio of 10:5:1.5 into a ball mill, and ball milling for 3 hours to obtain a mixture; the hard template is nano calcium carbonate; placing the mixture in a tubular furnace, using N2 to replace the air in the tubular furnace, and then introducing 1.5MPa of H2, heating at a rate of 4°C / min for the first time, and calcining for the first time after the temperature is raised to 800°C, and calcining for 3.5 hours to obtain activated alumina;

[0081] Disperse 50 mg of the activated alumina in 30 mL of deionized water, and use hydrochloric acid to adjust the pH to 3.0 to obtain an activated alumina dispersion; dissolve sodium tungstate dihydrate in deionized water to obtain a sodium tungstate solution; dissolve nickel acetate tetrahydrate in deionized water to obtain a nickel acetate tetrahydrate solution; mix the sodium tungstate solution and the nickel acetate tetrahydrate solution to obtain a tungsten-nickel metal solution; the molar mass ratio of tungsten to nickel in the tungsten-nickel metal solution is 3:1; mix the activated alumina dispersion with the tungsten-nickel metal solution, add ammonia water and dry in an oven to obtain the material to be calcined; The total mass of the tungsten and the nickel in the calcined material is 0.14 mg; the material to be calcined is placed in a tubular furnace again, and the temperature is increased for a second time at a rate of 8°C / min. After the temperature is increased to 800°C, a second calcination is carried out, and the intermediate is calcined for 2 hours to obtain an intermediate; 100 mL of a 35% by volume hydrochloric acid solution is added to the intermediate, and the metal-loaded mesoporous alumina is obtained by ultrasonication at a frequency of 100 Hz for 10 minutes; the metal-loaded mesoporous alumina is centrifuged, washed with deionized water, and dried to obtain a mesoporous catalyst based on activated alumina.

[0082] Examples 44-50

[0083] Different from Example 43, the specific preparation information is shown in Table 6.

[0084] Table 6 Information of mesoporous alumina treated with hydrochloric acid in Examples 44-50

[0085] Group Volume fraction of hydrochloric acid solution (%) Ultrasonic frequency (100HZ) Ultrasonication time (min) Embodiment 43 35 100 10 Embodiment 44 45 100 10 Embodiment 45 50 100 10 Embodiment 46 60 100 10 Embodiment 47 45 80 10 Embodiment 48 45 120 10 Embodiment 49 45 100 8 Embodiment 50 45 100 13 Comparative Example 9 45 100 30 Comparative Example 10 0 100 10

[0086] Comparative Example 11

[0087] Different from Example 43, no tetraethyl orthosilicate and tungsten nickel metal solution were added.

[0088] Embodiment 51

[0089] The content of L-acid was characterized by pyridine adsorption FT-IR. Agilent Cary 630 FT-IR was used for testing. The catalysts of Examples 43-50 and Comparative Examples 9-11 were vacuum treated at 320° C. for 3 h, then cooled to 200° C., adsorbed pyridine to saturation, and then desorbed until equilibrium was reached. Finally, the temperature was lowered to collect spectra, and the content of L-acid was calculated semi-quantitatively.

[0090] The content of B acid was characterized by NH3-TPD, and the test was performed using an AutoChem II 2920 fully automatic chemical adsorption instrument. The catalysts obtained in the examples and comparative examples were subjected to programmed temperature increase, and the gas adsorbed on the catalyst surface was removed to perform an NH3 adsorption-desorption test. After the desorption reached equilibrium, the total acid content was obtained by measuring the desorption amount of NH3. The test results are shown in Table 7.

[0091] The test results show that the B acid amount of the catalyst prepared in the embodiment is 1.93-2.85µmol / g, the L acid amount is 20.49-25.91µmol / g, and the total acid amount is 23.05-28.76µmol / g. The B acid amount is the acidic hydroxyl group on the surface of the aluminum oxide tetrahedron, which can provide hydrogen protons, and the L acid refers to the unsaturated coordinated cation, which can accept electron pairs. The aluminum oxide without metal loading and modification basically only has L acid (such as the result of comparative example 10). High B acid amount and low L acid amount are conducive to the catalysis of dehydrogenation and desulfurization reactions. The present invention uses hydrochloric acid solution for ultrasonic treatment, on the one hand, to remove the hard template calcium carbonate in the system, on the other hand, to introduce chlorine elements, and at the same time, tetraethyl orthosilicate is used to modify and load tungsten nickel metal on aluminum oxide, and the obtained catalyst B acid amount, L acid amount and total acid amount are all increased. In Examples 43-46, as the volume fraction of hydrochloric acid increases, the B acid amount gradually decreases after increasing. The test results of Examples 44, 47, and 48 show that the frequency of ultrasound needs to be within the range of 80-120HZ, and the mesoporous catalyst based on activated alumina obtained has a higher B acid amount, L acid amount, and total acid amount. The results of Examples 44, 49, and 50 show that the ultrasound time needs to be controlled within a reasonable range of 8-13min. If the ultrasound time is too long, as shown in Comparative Example 9, the loaded metal dissolves during the ultrasound process. In addition, the ultrasound time is too long, which causes the components of alumina to be damaged. Therefore, the B acid amount, L acid amount, and total acid amount all decrease, and the overall performance of the catalyst decreases. In summary, the catalyst prepared by the present invention has a high B acid amount, L acid amount, and total acid amount, and has good catalytic performance.

[0092] Table 7 Pyridine adsorption and infrared test results of catalysts of Examples 43-50 and Comparative Examples 9 and 10 (test conditions at 320°C)

[0093] Group B acid content (µmol / g) L Acid content (µmol / g) Total acid content (µmol / g) Embodiment 43 1.93 21.12 23.05 Embodiment 44 2.85 25.91 28.76 Embodiment 45 2.71 25.53 28.24 Embodiment 46 2.59 26.60 29.19 Embodiment 47 2.29 23.40 25.69 Embodiment 48 2.48 24.85 27.33 Embodiment 49 2.02 20.49 22.51 Embodiment 50 2.44 25.16 27.60 Comparative Example 9 1.75 19.70 21.45 Comparative Example 10 0.86 17.35 18.21 Comparative Example 11 0.01 12.18 12.19

[0094] Embodiment 52

[0095] Aluminum sec-butoxide was dissolved in isopropanol to obtain an aluminum sec-butoxide solution; the concentration of the aluminum sec-butoxide solution was 0.05 g / mL; 2.09 g of ethyl orthosilicate and 4.9 mL of deionized water were added to 200 mL of the aluminum sec-butoxide solution, and the mixture was hydrolyzed at 70° C. and 600 rpm for 3.5 h to obtain a mixed solution; the mixed solution was heated to 120° C. and subjected to hydrothermal reaction for 2 h to obtain a gel; the gel was vacuum filtered, washed, and dried to obtain silicon-pseudo-silicon water Aluminium stone; adding silica-pseudo-boehmite, hard template and pre-treated chitosan in a mass ratio of 10:5:1.5 into a ball mill, and ball milling for 3 hours to obtain a mixture; the hard template is nano-calcium carbonate; placing the mixture in a tubular furnace, using N2 to replace the air in the tubular furnace, and then introducing 1.5MPa of H2, heating at a rate of 4°C / min for the first time, and calcining for the first time after the temperature is raised to 800°C, and calcining for 4.0 hours to obtain activated alumina;

[0096] Disperse 50 mg of the activated alumina in 30 mL of deionized water, and use hydrochloric acid to adjust the pH to 3.0 to obtain an activated alumina dispersion; dissolve sodium tungstate dihydrate in deionized water to obtain a sodium tungstate solution; dissolve nickel acetate tetrahydrate in deionized water to obtain a nickel acetate tetrahydrate solution; mix the sodium tungstate solution and the nickel acetate tetrahydrate solution to obtain a tungsten-nickel metal solution; the molar mass ratio of tungsten to nickel in the tungsten-nickel metal solution is 11:9; mix the activated alumina dispersion with the tungsten-nickel metal solution, add ammonia water dropwise, and place in an oven to dry to obtain a material to be calcined; The total mass of the tungsten and the nickel in the material to be calcined is 0.14 mg; the material to be calcined is placed in a tubular furnace again, and the temperature is increased for a second time at a rate of 8°C / min. After the temperature is increased to 800°C, a second calcination is carried out, and the intermediate is calcined for 2 hours; 100 mL of a 45% by volume hydrochloric acid solution is added to the intermediate, and the metal-loaded mesoporous alumina is obtained by ultrasonication at a frequency of 100 Hz for 10 minutes; the metal-loaded mesoporous alumina is centrifuged, washed with deionized water, and dried to obtain a mesoporous catalyst based on activated alumina.

[0097] Examples 53-60, Comparative Examples 12-14

[0098] Different from Example 52, the following preparation conditions are changed, as shown in Table 8.

[0099] Table 8 Changes in the amount of tetraethyl orthosilicate and tungsten and nickel added in Examples 53-60 and Comparative Examples 12-14

[0100] Example Addition amount of tetraethyl orthosilicate (g) Metal addition amount of tungsten and nickel (mg) Embodiment 52 2.09 0.14 Embodiment 53 1.85 0.14 Embodiment 54 1.71 0.14 Embodiment 55 2.50 0.14 Embodiment 56 3.35 0.14 Embodiment 57 2.50 0.20 Embodiment 58 2.50 0.23 Embodiment 59 2.50 0.26 Embodiment 60 2.50 0.30 Comparative Example 12 0 0.20 Comparative Example 13 2.50 0 Comparative Example 14 0 0

[0101] Embodiment 61

[0102] The catalysts prepared in Examples 52-60 and Comparative Examples 12-14 were subjected to catalytic cycle performance tests. The specific test method is as follows: the desulfurization catalytic performance test of sulfur-containing dibenzothiophene was carried out according to the method and dosage of Example 42. After the test, the catalysts obtained in each example and comparative example were washed with deionized water and dried, and then re-tested for catalytic performance. A total of 10 catalytic cycle performance tests were carried out, and the conversion rate results are shown in Figure 3 middle.

[0103] like Figure 3 As shown, the conversion rate of the catalyst prepared in the embodiment of the present invention after the first catalysis is 60.5%-74.0%, the conversion rate after catalysis after 5 uses is 55.4%-69.5%, and the conversion rate after catalysis after 10 cycles is 44.2%-59.7%. Compared with the uncycled use, the conversion rate after 10 cycles is reduced by 18.5%-26.9%. In Examples 52-56, by changing the amount of tetraethyl orthosilicate introduced, the conversion rate of the catalyst obtained is different, and the conversion rate is in the range of 60.5%-73.1%. Comparison of the results of Examples 55 and 57-60 shows that the catalytic performance of the obtained catalyst is good by controlling the loading amount of tungsten and nickel metals in alumina, wherein the conversion rate of the catalyst of Example 57 after the first cycle is 73.8%, the conversion rate after 5 cycles is 68.9%, and the conversion rate after 10 cycles is 60.1%; the conversion rate of the catalyst of Example 60 after the first cycle is 74.0%, but after 10 cycles, the conversion rate of the catalyst decreases by 19.3%, and the conversion rate is 59.7%. Comparative Examples 12-14, without adding tetraethyl orthosilicate, tungsten and nickel metals, and without adding tetraethyl orthosilicate and metals, the conversion rate decreases compared with the examples, and the conversion rate of the obtained catalyst after 10 cycles is greatly reduced, as shown in Comparative Example 14, the catalytic conversion rate after 10 cycles is only 10.7%. The present invention modifies aluminum oxide by using tetraethyl orthosilicate, and loads metal tungsten and nickel. During the reaction process, Si, W and Ni replace the position of Al in a part of Al-O bonds, and protect the hydrolysis and degradation active sites of aluminum oxide. In addition, the formation of Al-O-Si bonds and Si-O-Si bonds can further increase the strength of the gel network structure, so that the catalyst can resist capillary force during the cyclic drying process, avoid cracking and collapse, and improve the stability of the catalyst, thereby improving the catalytic cycle performance of the obtained catalyst.

[0104] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a mesoporous catalyst based on activated alumina, characterized in that: The following steps are involved: Aluminum sec-butoxide is dissolved in isopropanol to obtain an aluminum sec-butoxide solution; 0-6.25 g of ethyl orthosilicate and 3.1-9.3 mL of deionized water are added to the aluminum sec-butoxide solution, and the mixture is hydrolyzed for 3.5-5 h under stirring and heating to obtain a mixed solution; the mixed solution is hydrothermally reacted for 2 h to obtain a gel; the gel is vacuum filtered, washed and dried to obtain silica-pseudo-boehmite; the silica-pseudo-boehmite, a hard template and a soft template are ball-milled in a mass ratio of 10:0-6.5:0-2 to obtain a mixture; the mixture is placed in a tubular furnace, and 0.3-1.5 MPa of H2 is introduced after N2 is used, and the temperature is first increased at a rate of 2.5-4°C / min, and calcined at a temperature of 600-800°C for 3.5-4.0 h to obtain activated alumina; The activated alumina is dispersed in deionized water, and the pH is adjusted to 1.5-4.0 to obtain an activated alumina dispersion; a sodium tungstate solution is mixed with a nickel acetate tetrahydrate solution to obtain a metal solution; the molar mass ratio of tungsten to nickel in the metal solution is 0-11:0-10; the activated alumina dispersion is mixed with the metal solution, ammonia water is added dropwise, and the mixture is placed in an oven to be dried to obtain a material to be calcined; the total mass of tungsten and nickel in the material to be calcined is 0.06-0.22 mg; the material to be calcined is placed in the tube furnace again, heated for a second time at a rate of 5-8°C / min, and calcined at 800°C for 2h to obtain an intermediate; a hydrochloric acid solution with a volume fraction of 0-60% is added to the intermediate, and ultrasonicated at a frequency of 80-120HZ for 8-30min, and then centrifuged, washed and dried to obtain the mesoporous catalyst based on activated alumina; The hard template is nano calcium carbonate; The soft template agent is any one of hexadecyltrimethylammonium bromide, pre-treated chitosan, polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer, polyether polyol and sodium dodecyl sulfate.

2. The method for preparing a mesoporous catalyst based on activated alumina according to claim 1, characterized in that: The concentration of the aluminum sec-butoxide solution is 0.05 g / mL; the dosage of the tetraethyl orthosilicate is 1.04-6.25 g.

3. The method for preparing a mesoporous catalyst based on activated alumina according to claim 1, characterized in that: The preparation method of the pre-treated chitosan comprises: adding hydrochloric acid solution to chitosan, stirring for half an hour to completely dissolve the chitosan, and then adding ammonia water to adjust the pH to 7 to obtain the pre-treated chitosan.

4. The method for preparing a mesoporous catalyst based on activated alumina according to claim 1, characterized in that: Silica-pseudo-boehmite, hard template and soft template are added into a ball mill in a mass ratio of 10:3-6.5:1-2.

5. The method for preparing a mesoporous catalyst based on activated alumina according to claim 1, characterized in that: The H2 is 0-1.5MPa.

6. The method for preparing a mesoporous catalyst based on activated alumina according to claim 1, characterized in that: The molar mass ratio of tungsten to nickel in the metal solution is 1-11:1-9.

7. The method for preparing a mesoporous catalyst based on activated alumina according to claim 1, characterized in that: Add 100 mL of a hydrochloric acid solution having a volume fraction of 35-60% to the intermediate.

8. A mesoporous catalyst based on activated alumina prepared by the method of claim 1, characterized in that: The mesoporous catalyst based on activated alumina is hydrolyzed with ethyl orthosilicate and aluminum sec-butoxide, mixed with a hard template and a soft template, and calcined by introducing H2 to obtain activated alumina; The activated alumina is impregnated with tungsten and nickel and then calcined, and then treated with hydrochloric acid solution, ultrasonicated, centrifuged, washed and dried to obtain the mesoporous catalyst based on activated alumina; the mesoporous catalyst based on activated alumina is prepared by the preparation method according to any one of claims 1 to 7; modified by the tetraethyl orthosilicate, the mesoporous catalyst based on activated alumina has a specific surface area of ​​278-372 m 2 ·g -1 , pore volume is 1.94-2.61cm 3 ·g -1 , the average pore size is 11.90-17.30nm; by changing the type and amount of the hard template and the soft template, the specific surface area of ​​the mesoporous catalyst based on activated alumina is 289-382m 2 ·g -1 , pore volume is 1.90-2.65cm 3 ·g -1 , the average pore size is 8.63-20.35nm; the mesoporous catalyst based on activated alumina is used for the hydrodesulfurization reaction of sulfur-containing dibenzothiophene, and the conversion rate of the raw material is in the range of 51.0%-75.3%; after using the hydrochloric acid solution and the ultrasonic treatment, the B acid amount of the mesoporous catalyst based on activated alumina is 1.93-2.85µmol / g, the L acid amount is 20.49-25.91µmol / g, and the total acid amount is 23.05-28.76µmol / g; the conversion rate of the mesoporous catalyst based on activated alumina after the first catalysis is 60.5%-74.0%, the conversion rate after catalysis after 5 uses is 55.4%-69.5%, and the conversion rate after catalysis after 10 cycles of use is 44.2%-59.7%.

Citation Information

Patent Citations

  • Transition metal phosphide hydrogenation catalyst and preparation method thereof

    CN103962165A

  • Heavy distillate oil hydrotreating catalyst and application thereof

    CN109833891A

  • Residual oil hydrodemetallization and desulfurization catalyst and preparation method thereof

    CN110201691A

  • A modified alumina support, its preparation method, and a hydrorefining catalyst

    CN111068750B

  • A supported nickel phosphide catalyst and its preparation method

    CN112295595B